Introduction to research strategies in cell biology - Pollard, Thomas D. (Henry Stewart Talks, 2021)
Genetic model organisms, Light microscopy, Fluorescence microscopy, Structure determination, Identification of molecular partners, Genome engineering, Physiological tests, Mathematical modelling